Odonata from protected areas in Colombia with new records and description of Cora verapax sp. nov. (Zygoptera: Polythoridae) (2018)
Colombia is one of the megadiverse countries in the world, but paradoxically it is one of the less explored. The recent red list assessments show the country has the highest number of endangered species in the Neotropical region. Nevertheless, the sampling effort is low especially in protected areas, which probably can harbor some of the rare species included in the red list. As a result of recent surveys in six protected areas of Colombia, we report twelve new records and describe Cora verapax sp. nov., a rare species, collected after more than 300 days of field surveys at the National Natural Park Tatamá. In addition, we compiled and mapped published Odonata records from 2001 until now for Colombian protected areas (136 spp.). Among the new records, some species were formerly known as endemics from Panama and Ecuador, and five species are reported for the first time inside protected areas, showing the importance of surveys in these special territories and bringing new data for conservation actions, as red list assessment or future management plans. Copyright © 2018 Magnolia Press